The Aggression of Human Activities on Chalanbeel a Threat on Wetland Environment: Study on Natore - Rajshahi Region of Bangladesh - Rahman, MM; Rahman, MR; Asaduzzaman, M (Journal of Science Foundation, 2013)
The Chalanbeel is the main wetland of Northwestern region of Bangladesh. It is not only the source of water but also one of the main sources of occupation for thousands of people. It supplies fresh water as well as abundant of aquatic resources. This wetland is the large source of native fishes. It plays a vital role to keep the environment of the surrounding vast region balanced. It makes the land fertile, alluvial and alive for whole the year round. It is also a large reservoir of biological diversity of this region. Recently the aggression of man on this great beel increases in such a rate that the overall environment of this wetland fall in a crisis. It is going to loss its tradition and pride of her resources. Specially the aggression of settlement and road construction along the wetland hampered the natural characteristics. Reach it and an investigation was conducted to study the overall condition of the wetland. The observation indicates horror news for both the environment and its inhabitant of the surrounding area. Soils under lower Natore- Rajshahi region of Bangladesh with a view to evaluate the agricultural potentiality, environmental condition and their management options. The studied wetlands were nutritionally very productive. It is believed that the soils of this area became enriched by siltation during flooding. Soil textural condition is very much appropriate for rice production in these basin floodplains. The content of nitrogen and boron is low. Probably, the denitrification process leads to the loss of nitrogen in these soils; other nutrients seem to be in balanced condition for the successful growth of deep water aman and boro rice. High yielding boro rice got preference over broadcast aman and aous as major rice crops in the area. Availability of irrigation water in the dry periods and deep inundation level in the monsoon may be the main cause of such cropping pattern. Recently a problem is found that is the gradual decreasing of crop production in these areas. Both soil fertility and water table deterioration is noticed as the main causes of this alarming news for North Bengal. As this area is consider as the rice production zone of Northern region of Bangladesh. Over pumping of water during dry season is also a cause to deteriorate the environmental balanced of this wetland. For the betterment of grater environment of this area it is essential to take necessary step to stop all kind of human aggression on wetland. Public awareness should increase about the matter. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14638 J. Sci. Foundation, 8(1&2): 151-159, June-December 2010